2002
DOI: 10.1614/0890-037x(2002)016[0116:irlcpm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Isoproturon-Resistant Littleseed Canarygrass (Phalaris minor) and its Response to Alternate Herbicides1

Abstract: Littleseed canarygrass, a troublesome wheat weed, has developed resistance against isoproturon in India. Laboratory, pot, and field experiments were conducted to quantify the level of isoproturon resistance in various littleseed canarygrass biotypes and to evaluate the response of isoproturon-resistant littleseed canarygrass to alternate herbicides. For quantification of resistance, 10 littleseed canarygrass biotypes were collected from fields with a varied history of cropping and herbicide use. Pot studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
76
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 13 publications
3
76
0
Order By: Relevance
“…The ability of dormant seeds to survive during rice period is a major fact for its prevalence in wheat-rice cropping system (Malik et al, 1998). Oad et al (2007) have reported that LCG infestation can reduce wheat yield by 35% and its heavy infestation might incur a complete crop failure (Chhokar and Malik, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of dormant seeds to survive during rice period is a major fact for its prevalence in wheat-rice cropping system (Malik et al, 1998). Oad et al (2007) have reported that LCG infestation can reduce wheat yield by 35% and its heavy infestation might incur a complete crop failure (Chhokar and Malik, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Heap (2015) reported that the herbicide selection pressure is continually increasing the resistant biotypes of different weeds. After the first case of P. minor resistance to isoproturon during 1995 in India, P. minor biotypes have developed resistance to ALS-inhibiting herbicide (sulfosulfuron), ACCase-inhibiting herbicides (clodinafop, fenoxaprop and tralkoxydim) and other herbicides with these modes of actions (Chhokar and Malik, 2002;Chhokar and Sharma, 2008;Gherekhloo et al, 2011). Many P. minor biotypes have evolved cross and multiple resistance to herbicides, having different modes of action in different parts of the world (Heap, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Chhokar and Malik 36 showed that under field conditions, at post-emergence isoproturon at 1,000 g/ha 32 d after sowing failed to control littleseed canarygrass and as a result wheat grain yield decreased by 65% compared with the weed-free control. Singh 37 reported that dry weight of S biotype was significantly reduced at 0.25 kg/ha of isoproturon.…”
mentioning
confidence: 99%
“…Extensive use of isoproturon over many years has led to the evolution of resistance in Phalaris minor in northwest India. 36,40 Therefore, continued reliance on isoproturon after the development of resistance resulted in a heavy build-up of Phalaris minor populations, as competition from other weeds was removed. This caused heavy yield losses in wheat.…”
mentioning
confidence: 99%
See 1 more Smart Citation